The Influence of Health Education On Breast Examination Itself On The Attitude of Early Detection of Young Women at Sma Negeri 4 Palu: Pengaruh Pendidikan Kesehatan Tentang Pemeriksaan Payudara Sendiri Terhadap Sikap Deteksi Dini Remaja Putri Di SMA Negeri 4 Palu - Pani, Widya (Poltekkes Kemenkes Palu, 2022)
Background: Breast cancer because it belongs to a type of malignant disease and ranks first in Indonesia after cervical cancer. The purpose in this study is to find out the influence of health education on breast examination itself (REALIZE) on the attitude of young women at Sma Negeri 4 Palu. Method: The type of research used is Pre-Experiment with the design of The One Group Pre-Test Post-Test. The sample number of 40 respondents used simple random sampling in grades X and XI. The data is analyzed using chi-square. Results: showed an increase in the percentage of respondents' attitudes before and after being given Health Education on Breast Self-Examination (23 respondents (57.5%) in pretest and 29 respondents (72.5%) in posttest. Conclusion: the provision of health education about breast examination itself shows an increase in good attitudes in adolescent girls at Sma Negeri 4 Palu. Advice is expected that many female students seek information from various media, so as to have a good understanding of SADAR.